Negative Transcriptional Regulation of the ilv-leu Operon for Biosynthesis of Branched-Chain Amino Acids through the Bacillus subtilis Global Regulator TnrA - Tojo, Shigeo (American Society for Microbiology, 2004)
The Bacillus subtilis ilv-leu operon is involved in the synthesis of branched-chain amino acids (valine, isoleucine, and leucine). The two- to threefold repression of expression of the ilv-leu operon during logarithmic-phase growth under nitrogen-limited conditions, which was originally detected by a DNA microarray analysis to compare the transcriptomes from the wild-type and tnrA mutant strains, was confirmed by lacZ fusion and Northern experiments. A genome-wide TnrA box search revealed a candidate box approximately 200 bp upstream of the transcription initiation base of the ilv-leu operon, the TnrA binding to which was verified by gel retardation and DNase I footprinting analyses. Deletion and base substitution of the TnrA box sequence affected the ilv-leu promoter activity in vivo, implying that TnrA bound to the box might be able to inhibit the promoter activity, possibly through DNA bending. The negative control of the expression of the ilv-leu operon by TnrA, which is considered to represent rather fine-tuning (two- to threefold), is a novel regulatory link between nitrogen and amino acid metabolism.